2023
DOI: 10.3390/life13071496
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment Approach, Emerging Therapies and New Horizons in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE), the prototype of systemic autoimmune diseases is characterized by extreme heterogeneity with a variable clinical course. Renal involvement may be observed and affects the outcome. Hydroxychloroquine should be administered to every lupus patient irrespective of organ involvement. Conventional immunosuppressive therapy includes corticosteroids, methotrexate, cyclophosphamide, mycophenolate mofetil, azathioprine, cyclosporine and tacrolimus. However, despite conventional immuno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 190 publications
1
3
0
1
Order By: Relevance
“…In this study, higher cumulative pulse methylprednisolone was associated with higher damage in lupus patients and that damage was expanded (increased) by 0.169 for every gram increase in the cumulative pulse level, which is in agreement with several studies that documented glucocorticoid-induced damage in lupus patients [ 14 18 ], describing up to 80% of organ damage in SLE being attributable to glucocorticoid use [ 19 ], with a clear dose-dependent relationship [ 4 ]. This also goes in line with the recommendation of limiting glucocorticoid use to the shortest possible time and the lowest dose possible [ 20 ]. The study by Badsha et al (2003) confirmed that 1–1.5 g methylprednisolone versus 3–5 g methylprednisolone total dosage over 3 days may show equal efficacy, but with higher complications and risk of infection observed with the higher (3–5 g) dose [ 7 ].…”
Section: Discussionsupporting
confidence: 78%
“…In this study, higher cumulative pulse methylprednisolone was associated with higher damage in lupus patients and that damage was expanded (increased) by 0.169 for every gram increase in the cumulative pulse level, which is in agreement with several studies that documented glucocorticoid-induced damage in lupus patients [ 14 18 ], describing up to 80% of organ damage in SLE being attributable to glucocorticoid use [ 19 ], with a clear dose-dependent relationship [ 4 ]. This also goes in line with the recommendation of limiting glucocorticoid use to the shortest possible time and the lowest dose possible [ 20 ]. The study by Badsha et al (2003) confirmed that 1–1.5 g methylprednisolone versus 3–5 g methylprednisolone total dosage over 3 days may show equal efficacy, but with higher complications and risk of infection observed with the higher (3–5 g) dose [ 7 ].…”
Section: Discussionsupporting
confidence: 78%
“…In the case of the positive association with photosensitivity, we have several hypotheses: Firstly, patients who are photosensitive tend to protect themselves more from ultraviolet radiation, a notorious trigger for both cutaneous and systemic flares in SLE [ 51 ]. Secondly, photosensitive patients are normally treated with drugs that are photoprotective like hydroxychloroquine, which is known to absorb ultraviolet light in the skin in a concentration-dependent manner; it has also been demonstrated to reduce mortality in SLE [ 52 ] by preventing flares and organ damage, and by having an effect in other comorbidities such as thrombosis or bone destruction [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two single-center retrospective studies reported the effectiveness of MTX in the treatment of discoid cutaneous and refractory systemic lupus. Lehman et al suggested that the use of MTX in pediatric SLE should be reserved for patients with severe nephritis who are resistant to cyclophosphamide [46][47][48].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%